2014
DOI: 10.1074/jbc.m114.595710
|View full text |Cite
|
Sign up to set email alerts
|

An Electrostatic Interaction at the Tetrahelix Bundle Promotes Phosphorylation-dependent Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Channel Opening

Abstract: The CFTR channel is an essential mediator of electrolyte transport across epithelial tissues. CFTR opening is promoted by ATP binding and dimerization of its two nucleotide binding domains (NBDs). Phosphorylation of its R domain (e.g. by PKA) is also required for channel activity. The CFTR structure is unsolved but homology models of the CFTR closed and open states have been produced based on the crystal structures of evolutionarily related ABC transporters. These models predict the formation of a tetrahelix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 48 publications
8
41
0
Order By: Relevance
“…Additionally, they provide evidence that inhibition does not rely on catalysis of sphingomyelin molecules that may be directly associated with gating CFTR channels.
Figure 2Inhibition is not membrane delimited: ( a ) CFTR currents recorded in the cell-attached configuration after activation with 0.2 mM IBMX were inhibited by 10 μg/ml SMase in the recording chamber suggesting activation of a signaling pathway that impinged upon the channels in the patch. ( b ) CFTR channels activated with 25 U PKA (expected activation of ~50% max) 36 , and recorded in the excised inside-out patch configuration were insensitive to 10 μg/mL SMase backfilled into the recording pipette. ( c ) Summary data showing fractional inhibition of currents in each configuration (p = 0.0021, unpaired t-test).
…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they provide evidence that inhibition does not rely on catalysis of sphingomyelin molecules that may be directly associated with gating CFTR channels.
Figure 2Inhibition is not membrane delimited: ( a ) CFTR currents recorded in the cell-attached configuration after activation with 0.2 mM IBMX were inhibited by 10 μg/ml SMase in the recording chamber suggesting activation of a signaling pathway that impinged upon the channels in the patch. ( b ) CFTR channels activated with 25 U PKA (expected activation of ~50% max) 36 , and recorded in the excised inside-out patch configuration were insensitive to 10 μg/mL SMase backfilled into the recording pipette. ( c ) Summary data showing fractional inhibition of currents in each configuration (p = 0.0021, unpaired t-test).
…”
Section: Resultsmentioning
confidence: 99%
“…Single-channel currents were recorded from inside-out patches using the Molecular Devices Axopatch 200B/pClamp 10 system (29). Currents were obtained under symmetrical Cl − at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The exact mechanistic origin of these effects is not clear but is consistent with the ICLs acting as a physical and functional link between the cytoplasmic NBDs and the channel gate within the MSDs (12,32,33). Because the present study was focused on the functional role of positively charged amino acid side chains within the ICLs in contributing to the Cl Ϫ permeation pathway, we sought to isolate the effects of MTS modification on Cl Ϫ permeation.…”
Section: Methodsmentioning
confidence: 99%
“…Early homology modeling suggested that the TM extensions that make up the ICLs may form a narrow central "funnel" that forms a pathway for Cl Ϫ movement between the cytoplasm and the transmembrane pore formed by the TMs (9,10). However, such a funnel model was not supported by experiments investigating the functional effects of mutations within the ICLs on Cl Ϫ permeation (11,12). The cytoplasmic entrance to the pore therefore remains the final unexplored region of the Cl Ϫ permeation pathway.…”
mentioning
confidence: 97%